Factors Influencing Dietary Diversity of Pregnant Women Attending Antenatal Care in Western Regional Hospital, Nepal: A Cross-sectional Study - Lama, Nishant; Lamichhne, Rajendra; Bhandari, Rajan; K.C., Shrejana; Sharma, Deepak; Bhandari, Gita Pun; Wagle, Rajendra Raj (Journal of Karnali Academy of Health Sciences, 2019)
Background: Diet during pregnancy is important to fulfill the nutritional demand of physiological changes as well as to create environment for fetal development. Studies have shown that micronutrient deficiencies are high due to low dietary diversity. In Nepal, meal diversity scores of mother and children are low. The situation of dietary diversity among pregnant women was unknown in Western Region of Nepal. Thus, this study was conducted togenerate evidence regarding status and determinants of dietary diversity among pregnant women. Methods: It was a cross sectional study. Systematic random sampling was done to select 282 pregnant women of third trimester attending antenatal care in Western Regional Hospital, Nepal. Semi-structured questionnaire, 24 hour recall tool andHousehold Food Insecurity Access Scale were used to collect information from participants. Univariate, bivariate and multivariate analysis was done to assess the status, association as well as strength of association between study variables respectively. Results: The mean (±SD) Women’s Dietary Diversity Score was 4.96 (±1.42). Pregnant women having education level < SLC compared to ≥ SLC were 74.7% less likely to have high dietary diversity to lowest dietary diversity (AOR: 0.253, CI: 0.103 – 0.620, p=0.003). Similarly, pregnant women having unpaid occupation of husbands compared to paid were 74.5% less likely to have high dietary diversity to lowest dietary diversity (AOR: 0.255, CI: 0.074 – 0.876, p=0.030). Conclusions: Consumption of medium dietary diversity was predominant among pregnant women. Education of the pregnant women and occupation of her husband werethe two significantly associatedfactors with dietary diversity.